Management of finger millet (Eleusine coracana) blast under field conditions by plant extracts - JOSHI, DEEKSHA; BHATT, J C; HOODA, K S; GUPTA, ARUN (The Indian Journal of Agricultural Sciences, 2012)
Antifungal activity of aqueous leaf extracts of eight plants against the pathogen Pyricularia grisea causing blast in finger millet was evaluated under in vitro and field conditions. In the in vitro screening, extracts of A. nilagirica, latifolia, L. camara, and P. hysterophorus showed significant hyphal growth inhibition (> 39.6%) over control with A. nilagirica showing highest inhibition (50.0% to 60.9%) at all concentrations. In general, the inhibitory activity of all eight extracts increased with increasing concentration. These four extracts were further evaluated as foliar sprays in field trials conducted over two crop seasons (2006 and 2007) along with the fungicide carbendazim for control of leaf, neck and finger blast of finger millet. Among the extracts, O. latifolia extract showed significantly high reduction in leaf (43.7%), neck (45.5%) and finger blast (28.1%) along with a significant yield increase (28.1%) over control in both crop seasons. Results indicate that crude aqueous extracts of O. latifolia can be used as an effective, economical and viable option for control of finger millet blast at farm level, especially under low input and/or organic farming conditions.